To solve the equation \( 44 = -11b + 33 \), we can follow these steps:
-
Subtract 33 from both sides: \[ 44 - 33 = -11b \] \[ 11 = -11b \]
-
Divide both sides by -11: \[ b = \frac{11}{-11} \] \[ b = -1 \]
Therefore, the solution is \( b = -1 \).
−11b+33
1 answer
To solve the equation \( 44 = -11b + 33 \), we can follow these steps:
Subtract 33 from both sides: \[ 44 - 33 = -11b \] \[ 11 = -11b \]
Divide both sides by -11: \[ b = \frac{11}{-11} \] \[ b = -1 \]
Therefore, the solution is \( b = -1 \).